Digital Activism in The Echo of #Kaburajadulu on Social Media - Rizski Pranata; Stanislaus Riyanta (International Journal Labs, 2025)
This study explores the phenomenon of digital activism in Indonesia through the viral hashtag #KaburAjaDulu, which emerged as a response to widespread dissatisfaction with political, economic, and social conditions. Unlike traditional forms of activism that rely on physical demonstrations and petitions, digital activism leverages social media platforms to mobilize collective action more rapidly and inclusively. By employing a qualitative approach and literature review, this research examines how #KaburAjaDulu reflects the frustrations of Indonesian youth and functions as a symbolic act of resistance against perceived systemic injustices. The findings reveal that the hashtag evolved into a digital movement that successfully captured public attention, particularly among young people, by fostering solidarity and stimulating critical discourse. The rapid spread of the campaign underscores the effectiveness of social media as a tool for amplifying voices and shaping public opinion. However, the long-term impact of such digital activism depends largely on institutional responses, especially from government actors. If these responses remain limited or dismissive, the campaign risks remaining symbolic rather than transformative. Conversely, constructive dialogue and policy adjustments could enhance its potential for lasting social change. This research concludes that while digital activism demonstrates significant potential in mobilizing public awareness and engagement, its success in driving tangible change requires sustained public participation, media amplification, and proactive institutional responses. Thus, #KaburAjaDulu not only highlights the power of social media in voicing dissent but also underscores the challenges of translating online momentum into concrete societal transformation.